2022
DOI: 10.1097/tp.0000000000004226
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of COVID-19 Among Vaccinated Solid Organ Transplant Recipients During the Omicron Wave

Abstract: T he Omicron variant has caused an unprecedented surge in SARS-CoV-2 infections among vaccinated people in the United States, owing to high transmissibility, immune evasion, and higher circulating antibodies required to achieve neutralization. Vaccine-derived protection is suboptimal among solid organ transplant recipients (SOTRs). [1][2][3][4][5] We studied frequency and severity of COVID-19 breakthrough during the US Omicron wave (December 25, 2021-March 1, 2022 in vaccinated SOTRs, focusing on the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…Overall, breakthrough COVID‐19 occurred in 8.9% of this population over 3 months of follow‐up that predominately overlapped a period of BA.2 and BA.4/5 sublineage predominance in the United States. These rates are similar to post‐vaccination breakthrough rates previously reported in our cohort during the BA.1 wave among those who did not receive T + C, albeit more frequent than rates observed during Alpha and Delta predominance 13 . Recent work by Al Jurdi et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, breakthrough COVID‐19 occurred in 8.9% of this population over 3 months of follow‐up that predominately overlapped a period of BA.2 and BA.4/5 sublineage predominance in the United States. These rates are similar to post‐vaccination breakthrough rates previously reported in our cohort during the BA.1 wave among those who did not receive T + C, albeit more frequent than rates observed during Alpha and Delta predominance 13 . Recent work by Al Jurdi et al.…”
Section: Discussionsupporting
confidence: 90%
“…As demonstrated, another consideration in interpreting breakthrough rates is potential changes in risk behavior following T + C, which may have led to increased exposure to SARS‐CoV‐2 and infections among those receiving PrEP (i.e., downward bias in drug effectiveness during follow‐up versus maintenance of “standard” behavior patterns). This, and the lack of a formal control group, and the fact that our parent cohort includes vaccinated SOTRs may limit the generalizability of reported breakthrough incidence rates to non‐recipients of T + C and unvaccinated SOTRs, although we were able to reference breakthrough rates among fully vaccinated SOTRs within the parent cohort during Omicron predominance who had not received T + C prophylaxis, and SARS‐CoV‐2 vaccination is universally accepted and recommended by transplant centers in the United States 13 . In our T + C population, 99% of SOTRs had received three or more SARS‐CoV‐2 vaccines prior to T + C, and 70% were seropositive for antibodies against the spike protein prior to receiving T + C, which is generally reflective of the target population (SOTRs) for whom T + C is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these observations may not correlate with clinical outcomes, given confounding from the increased transmissibility but attenuated virulence of Omicron strains [ 22 ]. For example, one study of vaccinated OTRs during the Omicron surge showed that seronegativity was not associated with risk of breakthrough SARS-CoV-2 infection, which, nonetheless, decreased with increasing antispike antibody titers [ 23 ]. Importantly, most of the aforementioned studies spanned earlier phases of the pandemic [ 2 , 4 , 6 , 9 , 11 ], with different circulating variants and potentially standards of care, which can affect base mortality rates [ 24 , 25 ].…”
mentioning
confidence: 99%
“…In a multicenter longitudinal cohort study of 1467 SOT recipients from United States, 150 (10.2%) reported a BI during the Omicron wave, with 11 (7.3%) hospitalizations and 2 (1.3%) deaths [ 10 ]. Among SOT recipients with serological available data, 96 of 666 (14.4%) were seronegative, 24% had medium-level AbR (anti-RBD, 250–2500 U/mL), and 47% had high-level AbR (anti-RBD, >2500 U/mL).…”
Section: Discussionmentioning
confidence: 99%